Comparative analysis of economic responses: Lebanon vs. Russia - Samar Abou Ltaif; Simona Mihai-Yiannaki (Cogent Social Sciences)
Purpose This study aims to compare the economic performance of Lebanon and Russia during periods of instability, focusing on the impact of economic factors on GDP fluctuations. While Russia has effectively managed economic challenges and maintained relative stability, Lebanon has faced significant financial turmoil. By examining factors and economic behaviors, the study seeks to provide insights into the distinct economic dynamics of these countries during periods of tension and instability.Design/Methodology/Approach The study utilizes multiple regression analysis with secondary data in SPSS to analyze the relationship between various economic factors and GDP. Additionally, Monte Carlo simulation is conducted based on the results of the regression analysis to further explore potential outcomes.Findings The study reveals that in Lebanon, trade imbalance, currency in circulation, inflation rate, and market exchange rate are negatively correlated with GDP, while personal remittances and interest rates show a positive correlation. In Russia, GDP is primarily influenced by the exchange rate and trade surplus, which is highly affected by oil exports.Originality This research contributes to the understanding of financial and economic tensions, providing insights into the economic performance of Lebanon and Russia amid instability. The findings can inform future strategic, monetary, and budgetary decisions, highlighting the need for innovative solutions to mitigate the negative impacts of financial and geopolitical instability on economic development and societal well-being.